Assessment of using solar system enhanced with MWCNT in PCM-enhanced building to decrease thermal energy usage in ejector cooling system. (1st September 2022) - Hai, Tao; Abidi, Awatef; Zain, Jasni Mohamad; Sajadi, S. Mohammad; Mahmoud, Mustafa Z.; Aybar, Hikmet Ş.
Abstract: In arid climate zones, more than 70% of electricity is used for cooling purposes on hot days of the summer. On the other hand, in these areas, the intensity of radiation is so high that it can be called a stable source of energy for cooling. This study is focusing on the ejector cooling method. Two procedures are employed to reduce energy consumption. In the first procedure, Phase Change Material (PCM) is installed in the building to decline heat transfer of the building and environment. In the second technique, solar system is added to the ejector to reduce much of the energy required by the generator. Then, to make this energy source more effective, multi-walled carbon nanotube (MWCNT) nanoparticles are added to the solar system to improve the solar energy absorption process. Because of adding PCM, energy transfer of the building was dropped by 16.3% in hot in Apr–Sep. Due to installing a solar system and integrating it with ejector, energy usage drops by 94.5 kW h per square meter. In the second procedure, MWCNT at 0.01–0.1 vol% were loaded into collectors and boosted the solar absorption which consequently declined the generator required thermal energy by 18.8%. Highlights: Focusing on the ejector cooling method, PCMs, solar system and energy consumption. Because of adding PCM, energy transfer of the building was dropped by 16.3%. Due to installing a solar system and integrating it with ejector, energy usage drops by 94.5 kW h/m 2 .